Narrative cultures and the aesthetics of religion - Johannsen, Dirk (Method & theory in the study of religion / Supplements, 2020)
"Narrative Cultures and the Aesthetics of Religion presents the aesthetics of narrative in religious contexts by approaching narrative acts as situated modes of engaging with reality, equally shaped by the immersive character of the stories told and the sensory qualities of their performances. Introducing narrative cultures as an integrative framework of analysis, the volume builds a bridge between classical content-based approaches to narrative sources and the aesthetic study of religions as constituted by sensory and mediated practices. Studying stories in conjunction with the role performative acts of storytelling play in the cultivation of the senses, the contributors explore the efficacy of storytelling formats in narrative cultures from Antiquity until today, in regions and cultures across the globe"--